2020
DOI: 10.1016/j.jseint.2020.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Early detection and treatment of complications in the fingers and hand after arthroscopic rotator cuff repair

Abstract: Background Complications in the fingers and hand after arthroscopic rotator cuff repair (ARCR) have been reported to include carpal tunnel syndrome (CTS), flexor tenosynovitis (TS), and complex regional pain syndrome. These studies were conducted retrospectively; however, the reported complications have not been examined prospectively. The aim of this study was to evaluate the outcomes of early detection and treatment of the complications after ARCR. Methods Forty-six p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Among them, the diagnosis was CTS in 2 hands, TS in 15 hands, and both CTS and TS in 3 hands; none of the hands exhibited CRPS. In our retrospective 4 and prospective 5 studies, we also reported that the complications of the fingers and hand that occurred after ARCR were mainly CTS or TS and that none of the hands exhibited CRPS after ARCR. Our current and previous studies suggest that CTS or TS can easily occur after ARCR.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Among them, the diagnosis was CTS in 2 hands, TS in 15 hands, and both CTS and TS in 3 hands; none of the hands exhibited CRPS. In our retrospective 4 and prospective 5 studies, we also reported that the complications of the fingers and hand that occurred after ARCR were mainly CTS or TS and that none of the hands exhibited CRPS after ARCR. Our current and previous studies suggest that CTS or TS can easily occur after ARCR.…”
Section: Discussionmentioning
confidence: 69%
“…In our study, 20 patients (20 hands) (40%) had complications of the fingers and hand after ARCR, with a frequency higher than that reported in previous studies on CTS, TS, and CRPS, which ranged from 0% to 35% after ARCR. 1 , 4 , 5 , 14 , 18 , 23 This relatively high frequency might be because we included slight symptoms as complications. By including these symptoms, we were able to diagnose and treat them to prevent them from worsening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harada et al [ 26 , 27 ] reported that the most common complication with hand symptoms after ARCR is flexor tenosynovitis followed by carpal tunnel syndrome, and prompt treatment with corticosteroid injections is recommended. Thus, the possibility that hand lesions after ARCR may be influenced by other diseases presenting with CRPS-like symptoms is becoming clearer.…”
Section: Discussionmentioning
confidence: 99%
“…Harada et al [26,27] reported that the most common complication with hand symptoms after ARCR is flexor tenosynovitis https://doi.org/10.5397/cise.2021.00080…”
mentioning
confidence: 99%